Systemic Chemotherapy prior to Cytoreductive Surgery and HIPEC for Carcinomatosis from Appendix Cancer: Impact on Perioperative Outcomes and Short-Term Survival - Lana Bijelic; Anjali S. Kumar; O. Anthony Stuart; Paul H. Sugarbaker (Gastroenterology Research and Practice)
Background and Objectives. Systemic chemotherapy administered prior to cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (HIPEC) for peritoneal mucinous adenocarcinoma of appendiceal origin (PMCA) is associated with a significant rate of histological response. The impact of preoperative systemic chemotherapy (PSC) on intraperitoneal tumor burden, completeness of cytoreduction, and perioperative complications is unknown. Methods. We analyzed prospectively collected data from our HIPEC database. Thirty-four patients with PMCA were prospectively recruited and treated with PSC. Perioperative variables and survival in this group of patients were compared against 24 patients with PMCA who did not receive PSC. Results. Ten of 34 patients (29%) receiving PSC had a complete or near complete histological response. Patients receiving PSC had a lower peritoneal carcinomatosis index, required fewer peritonectomies and visceral resections, and achieved complete cytoreduction more frequently compared to patients with no preoperative chemotherapy. The incidence of perioperative complications and survival were not significantly different between the two groups. However, patients with complete histological response had better overall survival compared to patients without complete response. Conclusions. Preoperative systemic chemotherapy in appendix-originated PMCA is associated with a significant rate of histological response which may reduce the tumor burden, facilitate less aggressive and more complete CRS, and improve short-term survival in patients with a significant histological response.